Prognostic Value of Syndecan-1 in the Prediction of Sepsis-Related Complications and Mortality: A Meta-Analysis - Sun, Ting; Wang, Yuqiong; Wu, Xiaojing; Cai, Ying; Zhai, Tianshu; Zhan, Qingyuan (Frontiers in Public Health, 2022)
Aim Syndecan-1 (SDC-1) has been shown to have a high predictive value for sepsis development, though uncertainty around these results exists. The aim of this meta-analysis was to assess the prognostic ability of SDC-1 in predicting sepsis-related complications and mortality. Methods We searched PubMed, EMBASE, Cochrane Library, and Google Scholar databases from January 01, 1990, to March 17, 2021, to identify eligible studies. The search terms used were “SDC-1,” “sepsis,” “severe sepsis,” and “septic shock,” and a meta-analysis was performed using the RevMan 5.4 software. Results Eleven studies with a total of 2,318 enrolled patients were included. SDC-1 concentrations were significantly higher in the composite poor outcome group [standardized mean difference (SMD) = 0.55; 95% CI: 0.38–0.72; P < 0.001] as well as in deceased patients (SMD = 0.53; 95% CI: 0.40–0.67; P < 0.001), patients with septic shock (SMD = 0.81; 95% CI: 0.36–1.25; P < 0.001), and patients with acute kidney injury (SMD = 0.48; 95% CI: 0.33–0.62; P < 0.001). Statistical significance was also found in the subgroup analysis when stratified by different sepsis diagnostic criteria. Conclusion Baseline SDC-1 levels may be a useful predictor of sepsis-related complications and mortality. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021246344, PROSPERO, identifier: CRD42021246344.